Indeterminacy, Ultimacy, and the World: the Self-Creation of Religious Pluralism through Community and Creation - Chicka, Benjamin James (Sophia, 2010)
Common arguments for truth in religious pluralism absolutize an ultimate or lived component of religion, reducing a positive affirmation of plurality to deeper unity or exclusion. The arguments of John Hick, William Connolly, Nicholas Rescher, and S. Mark Heim fall into such a trap. By considering how an indeterminate concept of ultimacy, proposed by Robert C. Neville, fares against the problems their arguments raise, it will be shown that such a concept of ultimacy can both give rise to and grow out of communal experiences and the nature of the world. The indeterminate ultimate, communal experiences, and the world pluralize themselves once understood in mutual relation.